Media Sosial sebagai Sarana Pemasaran UMKM di Era Digital (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Technological advancements are making various activities easier, including product marketing for micro, small, and medium enterprises (MSMEs). One benefit of these technological advancements is the opportunity for MSMEs to market their products widely, effectively, and cost-effectively thru social media marketing. UMKM Bolu Gulung Hj. Enong is in a business position that is starting to become popular. The desire to remain a frequently discussed business and reach a wide range of consumers led to the implementation of optimal marketing strategies using social media. Utilization of social media to introduce products. The research method uses literature studies, article collection with relevant title selection, and articles published within the timeframe of 2020-2025. Conclusion: Social media reaches a wide market, quickly and cheaply. MSMEs like Bolu Gulung Hj. Enong, in the food industry, can promote their products thru social media to reach target markets in other regions and target users in various areas. However, there are several challenges with using social media marketing strategies, namely the business's lack of digital knowledge, communication errors, and the fact that it makes it easier for competitors to copy marketing strategies.